Nurses on Social Media: Global Challenges and Pakistani Context - Muhmooda Abdul Razzaque; Rukhsana Muhammad Haroon (Journal of the Pakistan Medical Association, 2024)
Social media has become a global phenomenon, impacting the nursing profession worldwide. While nurses on social media face universal challenges, each country also has unique factors that influence the nature of these challenges. This editorial highlights the global challenges nurses face on social media and discusses the specific context of Pakistan, shedding light on the challenges experienced by nurses in this country. Nurses worldwide face the challenge of protecting patient confidentiality and privacy when using social media. The global nature of social media platforms means that nurses must be mindful of privacy laws and regulations specific to their country. Ensuring adherence to ethical guidelines and implementing stringent privacy measures is crucial to safeguard patient information across borders1. Continued...